Keragaman Serangga yang Terperangkap pada Cairan Beberapa Spesies Kantong Semar (Nepenthes spp.) di Kota Subulussalam, Provinsi Aceh - Liyana; Herlina Putri Endah Sari; Kartika Aprilia Putri (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Subulussalam City has an area consisting of residential, plantation, and forest. This condition affects the diversity and distribution of flora and fauna. One of the floras in Subulussalam City is Nepenthes spp., which has the unique ability to trap insects. The species of Nepenthes that have been found in Subulussalam City are N. ampularia, N. gracilis, N. mirabilis, and N. reindwardtiana. There are several insects trapped in the Nepenthes pouch, but the species is not yet known. Therefore, it is necessary to conduct a study on the diversity of insects trapped in the Nepenthes pouch in the Sultan Daulat Forest Area. The purpose of this study was to determine the species of insects trapped in the liquid of Nepenthes spp. in Sultan Daulat District, Subulussalam City. Data collection in the research area was conducted by exploring 1 km along the border road of Pulo Kedep Village and Sepadan Village. The purposive sampling method involved observing the presence of Nepenthes by walking. If Nepenthes is found at the research location, documentation is carried out on it. Then, the liquid from the upper and lower bags of Nepenthes is poured into separate plastic bags, labeled, and the data is recorded. The study identified 22 insect species, comprising 20 genera, 10 families, and four orders, with the most common order being Hymenoptera.